Optical properties and emission cross-section of neodymium nanoparticles doped tellurite glass coated with graphene oxide/reduced graphene oxide - Hafizah Rajaa Shaari (Tanjong Malim, 2024)
Optical properties and emission cross-section of neodymium nanoparticles doped tellurite glass coated with graphene oxide/reduced graphene oxide by Hafizah Rajaa Shaari